Biomechanical study on lower limbs in forehand tennis volley - Wang, X. (Medicina dello Sport, 2020)
BACKGROUND: Tennis, as a complex ball game, requires the participation of muscles and joints. Forehand volley is one of the most important tennis skills, and is also one of the main means to gain scores. METHODS: In order to improve the technique of forehand volley more effectively and reasonably, the kinematics and dynamics characteristics and parameters of lower limbs of 10 second-level athletes of the College of Physical Education at Liaocheng University in forehand tennis volley movement were detected by infrared high-speed motion capture system and three-dimensional dynamometer. RESULTS: The results demonstrated that the forehand volley action of lower limbs was divided into two stages, the cushioning stage and the pedaling and stretching stage. In the cushioning stage, the three-dimensional angles of the hip and knee joints were not significantly different with the increase of initial distance; the joints were in a bending state and the knee joints had outward extorsion while landing. In the pedaling and stretching stage, the three-dimension angle of the knee joint was not significantly different, and the hip flexion angle became significantly different with the increase of the initial distance, whereas the abduction and lateral rotation angles were the opposite. The reactive force of the ground to the lower limbs varied when the initial position was different. The farther the distance, the greater the vertical reactive force. At the beginning of the movement, the growth rate of the vertical and horizontal reactive force tended to be the same with the increase of the distance. CONCLUSIONS: In the forehand tennis volley, athletes have different changes in the joints of their lower limbs at different movement stages and have different stresses on their lower limbs at starting positions. This study has important reference value for the training of forehand tennis volley.